Digitalni nacionalizem - Bajt, Veronika (Teorija in praksa, 2014)
Drawing on an analysis of websites of political actors in Slovenia, the article notes that in the Slovenian context online national symbolism is associated with the civic idea of belonging to a political community of citizens, and less to ethnonationalism. This means that state institutions are modest in their use of national symbolism in the online environment given that it is only present on the websites of one-third of the analysed political actors. Introducing the term "digital nationalism", the article uses theories of nationalism to explain the apparent divide between digitalised nationalist archaism and online civic actualisation.
Keywords: Državni simboli; Nacionalizem; National emblems; Nationalism; Political institutions; Politične institucije; Slovenia; Slovenija; Spletišča; svetovni splet; Web sites